The role of short-term accommodations on the place brand and real estate development of urban areas: A case study of Malate, Manila - Virgilio Angelo Gelera Gener (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: This research looks into how vacation rentals have impacted the image of Philippine cities and the growth of the real estate market there. Through a combination of surveys, in-depth interviews, and focus groups, this study seeks to understand how stakeholders perceive these accommodations regarding their impact on a community’s place brand and land value. Methodology: In this study, we used qualitative methods. Employees and officials of certain developers and identified government offices were interviewed for this study. Findings: The survey found that despite being categorized as